Supplementation with postbiotic from Bifidobacterium Breve BB091109 improves inflammatory status and endocrine function in healthy females: a randomized, double-blind, placebo-controlled, parallel-groups study - Motei, Diana Elena; Beteri, Beyda; Hepsomali, Piril; Tzortzis, George; Vulevic, Jelena; Costabile, Adele (Frontiers in Microbiology, 2023)
This study evaluated the effects of dietary supplementation with a postbiotic extract of Bifidobacterium breve BB091109 on pro-inflammatory cytokines levels and markers of endocrine function. A prospective, double-blind, placebo-controlled, randomized, single-centered, parallel study was conducted on a group of 40-55-year-old females. The study included 30 healthy females, divided into two groups: a supplement (n=20) and a placebo (n=10) groups. Blood and saliva samples were collected at baseline (wk0), after 4 weeks (wk 4) and 12 weeks (12wk) of daily supplementation (500 mg), and 4 weeks (wk 16) after termination of supplementation. The levels of fasting CRP, IL-6, IL-10, TNF-a, IFN-g, DHEA, estradiol, estriol, progesterone, cortisol and human growth hormone were analysed. The results revealed a significant effect of the 90-day supplementation with B. breve postbiotic extract on changes in CRP, IL-6 levels, DHEA, estradiol and estriol. In conclusion, the supplementation with the B. breve postbiotic extract improved endocrine function in females over 40 years old and induced protective changes in inflammatory markers. These findings highlight the potential health benefits of this supplementation in promoting hormonal balance and reducing inflammation in this population.